Evaluation of fungicides against mycoflora associated with castor seed - Nagaraja, O; Krishnappa, M (Indian Journal of Plant Protection, 2023)
A total of 130 castor seed samples were collected from different agro climatic regions of Karnataka during 2010-2011. All the seed samples were tested for associated mycoflora using standard blotter method (SBM). The seeds were treated with fungicides at different concentrations (0.5%, 1.0%, 1.5% and 2.0%) and the associated mycoflora were recorded at seven days after incubation. Among the tested fungicides, Carbendazim and Captra were found superior for the inhibition of seed-borne pathogens and increased the germination at 2.0 percent concentration.